2021
DOI: 10.1016/j.ebiom.2021.103378
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognostic factors in Covid-19: A prospective cohort study

Abstract: Background: Mortality rates are high among hospitalized patients with COVID-19, especially in those intubated on the ICU. Insight in pathways associated with unfavourable outcome may lead to new treatment strategies. Methods:We performed a prospective cohort study of patients with COVID-19 admitted to general ward or ICU who underwent serial blood sampling. To provide insight in the pathways involved in disease progression, associations were estimated between outcome risk and serial measurements of 64 biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 42 publications
5
88
0
1
Order By: Relevance
“…Absolute values of inflammatory markers such as PCT and CRP can be readily influenced by disease-modifying agents as we demonstrated earlier [ 23 ]. Previously published patient level data derived from the first wave of the pandemic showed that PCT levels can be sporadic and highly variable, with levels elevated even in the absence of confirmed infection [ 22 , 23 , 24 ]. As such, our study employed a predetermined rise in PCT, utilising trends in serial PCT levels rather than a critical tipping point as an indicator for secondary infection, which could be adopted in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Absolute values of inflammatory markers such as PCT and CRP can be readily influenced by disease-modifying agents as we demonstrated earlier [ 23 ]. Previously published patient level data derived from the first wave of the pandemic showed that PCT levels can be sporadic and highly variable, with levels elevated even in the absence of confirmed infection [ 22 , 23 , 24 ]. As such, our study employed a predetermined rise in PCT, utilising trends in serial PCT levels rather than a critical tipping point as an indicator for secondary infection, which could be adopted in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 was defined as a positive severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) polymerase chain reaction (PCR). IL-6 and IL-10 were measured in serial blood samples from March to May 2020 [4]. Patients who died during admission were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Readmissions and mortality after hospital discharge were ascertained by contacting the general practitioner (GP). Biomarker measurements were done by using a Luminex platform [4]. Normally distributed data were analyzed by a t-test and nonparametric continuous data by Mann-Whitney U test.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the authors suggested that endothelial dysfunction might not be characteristic of severe COVID-19 early after ICU admission [ 3 ]. Based on the complex pathophysiology of COVID-19, it seems that endothelial dysfunction may not be pivotal for the development of severe disease, since several other pathways, such as chemotaxis, interleukin production and immunothrombosis also play a significant role [ 4 ].…”
mentioning
confidence: 99%